Peter Spier's circus! - Spier, Peter (New York : Dell Dragonfly Books, 2002)
A traveling circus arrives, sets up its village of tents, performs for the crowd, and then moves on again.
Publisher's Weekly
School Library Journal
Wilson's Children
4.8
K-3.
K-3
Keywords: Circus -- Fiction; Circus -- Fiction; Circus -- Fiction; Picture books for children